Is the pollination biology of Bathysa and Schizocalyx consistent with their segregation? A first approach for two sympatric species in southeastern Brazil. Issue 5 (15th August 2013) - Freitas, Leandro; Andrich, Mariana
Abstract: Tribe Condamineeae appears to be well supported in recent phylogenetic studies. However, the species of Bathysa were divided into two clades, leading to restoration of Schizocalyx . We studied the reproductive biology of one species from each clade, which occur sympatrically in the montane Brazilian Atlantic forest. Flowering overlap was short (from December to March in B . australis and from February to June in S . cuspidatus ). The flowers of both species are protogynous and homostylous and last for about 3 days. The unit of pollination in B. australis is the inflorescence. Its flowers have a greenish hypocrateriform corolla (tube about 5 mm long) and were mainly pollinated by bees and wasps in search of nectar. Schizocalyx cuspidatus has white flowers with an infundibuliform corolla (tube about 8 mm long), and its main pollinators were stingless bees in search of pollen. The pollination systems of the two species did not correspond to their pollination syndromes. Morphological differences between Bathysa and Schizocalyx were reflected in their pollination systems, with greater phenotypic specialization in S. cuspidatus, the flowers of which offer pollen as the main resource, an unusual feature within Rubiaceae. Schizocalyx cuspidatus showed higher reproductive capacity by having more inflorescences per plant, more ovules per flower, and twice the proportion of flowering individuals. However, the reproductive efficiency (fruit set, seed/ovule ratio) did not differ between the species, despite the higher frequency of visits by pollinators to S. cuspidatus . Self‐compatibility in B. australis and self‐incompatibility in S. cuspidatus seem to explain these results.